2006
DOI: 10.1080/13547500600733622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the urinary excretion time courses of pyrene-1,6-dione, pyrene-1,8-dione and 1-hydroxypyrene in rats intravenously exposed to pyrene

Abstract: The urinary excretion time courses of pyrene-1,6-dione (P16D), pyrene-1,8-dione (P18D) and 1-hydroxypyrene (1-OHP) were compared in Sprague-Dawley and Wistar rats. Groups of five male rats, of about 200 g of body weight, were injected intravenously with 0.05, 0.5, 5 and 50 micromol pyrene kg-1 of body weight. Urine was collected at 2, 4, 6, 8, 10, 12, 18, 24, 30, 42 and 48 h post-dosing. Pyrene metabolites were measured by high-performance liquid chromatography (HPLC)/fluorescence after enzymatic hydrolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It can also be reasonably assumed that other metabolites of pyrene, different from 1-OH-pyrene, represent a major source of pyrene metabolites as compared to 1-OH-pyrene. Whereas the first assumption is actually generally recognized in the literature, the second assumption can be supported by the recent studies of Ruzgyte et al , . These authors recently showed that about 27% of pyrene intravenously injected into Sprague–Dawley rats was metabolized under the pyrene-1,6-dione and pyrene-1,8-dione forms against about 1% only under the 1-OH-pyrene form (analysis in urine over a 48 h sampling period).…”
Section: Resultsmentioning
confidence: 85%
“…It can also be reasonably assumed that other metabolites of pyrene, different from 1-OH-pyrene, represent a major source of pyrene metabolites as compared to 1-OH-pyrene. Whereas the first assumption is actually generally recognized in the literature, the second assumption can be supported by the recent studies of Ruzgyte et al , . These authors recently showed that about 27% of pyrene intravenously injected into Sprague–Dawley rats was metabolized under the pyrene-1,6-dione and pyrene-1,8-dione forms against about 1% only under the 1-OH-pyrene form (analysis in urine over a 48 h sampling period).…”
Section: Resultsmentioning
confidence: 85%
“…This suggests that peak G represents an isomer of PYDS other than 1,6-PYDS, and therefore a novel biotransformation product. In all cases in the literature where pyrenediol or its conjugates were detected as metabolites of PY they were identified as either the 1,6 or the 1,8 isomers [10,11,51]. It is therefore likely that peak G represents 1,8-PYDS.…”
Section: Lc-ms/ms Identification Of Metabolitesmentioning
confidence: 97%
“…biotransformation products of pyrene have also been identified in other organisms, including humans [56], rats [51] and clams [29] but so far not in finfish.…”
Section: Compoundmentioning
confidence: 97%
“…Other biotransformation products of 1-OHP that have been identified are 1,6-and 1,8-dioxygenated metabolites of pyrene. Ruzgyte et al (2005Ruzgyte et al ( , 2006 showed significant excretion of pyrene-1,6-and pyrene-1,8-dioxygenated metabolites in urine of rats after i.v. injection of pyrene.…”
Section: Physical-chemical Datamentioning
confidence: 98%